Perspektif Inovasi Dalam Aplikasi “Dukcapil Dalam Genggaman V.2” Di Dinas Kependudukan Dan Pencatatan Sipil Kota Surakarta - Yudhanto, Bayu Tri; Pramono, Joko; Suhita, Damayanti (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
The development of Information and Communication Technology (ICT) in Indonesia, driven by Law No. 23 of 2014, has spurred bureaucratic reforms, including in population administration. The city of Surakarta is one of the cities that has successfully implemented E-Government, with the